Comparison study for the recovery of bioactive compounds fromTribulus terrestris, Panax ginseng, Gingko biloba, Lepidium meyenii, Turnera diffusa and Withania somniferaby using microwave-assisted, ultrasound-assisted and conventional extraction methods - Tsaltaki, C.; Katsouli, M.; Kekes, T.; Chanioti, S.; Tzia, C.
Heat reflux (CONV), Soxhlet (SOX), microwave-assisted (MAE)and ultrasound-assisted (UAE)extraction methods, using ethanol, water and their mixtures, were studied for the recovery of bioactive compounds from Tribulus terrestris, Panax ginseng, Gingko biloba, Lepidium meyenii, Turnera diffusaandWithania somnifera. The study revealed that SOX method achieved extracts with the highest yieldTPCin terms of the total phenolic content (TPC)(66.65 ± 1.50
Keywords: ULTRASOUND ASSISTED EXTRACTION; MICROWAVE-ASSISTED EXTRACTION; HEAT REFLUX EXTRACTION; SOXHLET; HPLC; HERBS